Answer :

Given 3x – y = 7 … (1)


2x + 4y = 0 … (2)


Expressing y of equation (1) in terms of x,


3x – y = 7


3x - 7 = y … (3)


Substituting (3) in (2),


2x + 4y = 0


2x + 4 (3x – 7) = 0


2x + 12x – 28 = 0


14x – 28 = 0


14x = 28


x = 2


Substituting x value in (3),


3x – 7 = y


3 (2) – 7 = y


y = -1


By solving, we get x = 2 and y = -1.


Justification:


Generally, we substitute x = 0 or y = 0 in the given linear equations to get y and x. So we get two points on the straight line. To find more points on the line, take different values of x related to it, we get different values for y from the equation.


We get the following tables for the given linear equations.


For 3x – y = 7


y = 3x – 7



For 2x + 4y = 0


x = -2y




Plotting these points on a graph and joining them, we get two straight lines.


From the graph, we can see that both lines intersect at (2, -1), hence the solution to this pair is (2, -1).


Hence x and y values satisfy equations (1) and (2).


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Equations of MotionEquations of MotionEquations of Motion41 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Let us write the West Bengal Mathematics

Let us solve the West Bengal Mathematics

Let us draw the gWest Bengal Mathematics

Let us solve the West Bengal Mathematics

Let us draw the gWest Bengal Mathematics

Let us draw the gWest Bengal Mathematics

Let us draw the gWest Bengal Mathematics

Let us express thWest Bengal Mathematics

Let us express thWest Bengal Mathematics

Let us express thWest Bengal Mathematics